“Guidelines Recommendations on the Treatment of Tricuspid Regurgitation. Where Are We and Where Do We Go With Transcatheter Valve Intervention” - Vahanian, Alec; Brochet, Eric; Juliard, Jean-Michel (Frontiers in Cardiovascular Medicine, 2018)
Tricuspid regurgitation (TR) is an important clinical problem because it is frequent and carries a poor prognosis when it is left uncorrected. However, there is still a lack of awareness of tricuspid disease in the medical community. The indications for evaluation and surgical interventions in patients with TR were recently updated in the ESC/EACTS guidelines. Transcatheter tricuspid valve intervention (TTVI), almost exclusively valve repair, is at an early stage of development as only a few hundreds of patients have been treated. The first-in-man valve implantation was very recently performed. The recent ESC/EACTS Guidelines state that “The potential role of transcatheter tricuspid valve treatment in high-risk patients needs to be determined.” We shall review here which lessons of interest for TTVI can be learned from the Guidelines as regards evaluation and indications for surgery and try to imagine what could be the place of TTVI in the Guidelines in the future.